2020
DOI: 10.2147/idr.s277890
|View full text |Cite
|
Sign up to set email alerts
|

<p>Occurrence of Multi-Drug Resistant <em>Escherichia Coli</em> and <em>Escherichia Coli</em> O157:H7 in Meat and Swab Samples of Various Contact Surfaces at Abattoir and Butcher Shops in Jimma Town, Southwest District of Ethiopia</p>

Abstract: Background Raw meat is one of the commonly consumed traditional diets in Ethiopia. However, unhygienic processing and distribution practices are risky for contamination of meat leading to human infection. This study was conducted to assess the presence of multi-drug resistant E. coli with special emphasis on E. coli O157:H7 from meat of cattle and swab samples at abattoir houses and butcher shops in Jimma town, Southwest district of Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
5
12
1
Order By: Relevance
“…This variation might be due to the differences in the hygienic and sanitary practices in the butcher shops especially poor hand washing practices. Studies conducted in Malaysia [7], Ghana [33] and Jimma [34] showed the prevalence of salmonella species to be 10%, 30%, and 11.3% respectively which were higher than the current study. This difference might be due to hygiene and sanitation practice, methodology differences in sample collection and processing procedure.…”
Section: Plos Onecontrasting
confidence: 89%
“…This variation might be due to the differences in the hygienic and sanitary practices in the butcher shops especially poor hand washing practices. Studies conducted in Malaysia [7], Ghana [33] and Jimma [34] showed the prevalence of salmonella species to be 10%, 30%, and 11.3% respectively which were higher than the current study. This difference might be due to hygiene and sanitation practice, methodology differences in sample collection and processing procedure.…”
Section: Plos Onecontrasting
confidence: 89%
“…This study revealed an overall positivity rate of 24.6% for E. coli . This finding was in line with the reports of Bedasa et al ( 57 ) (20%), Sebsibe and Asfaw ( 58 ) (20.2%), Messele et al ( 59 ) (21.6%), Tadese et al ( 60 ) (23.4%), Abebe et al ( 61 ) (23.7%), Haileselassie et al ( 10 ) (27.3%), and Haftu et al ( 62 ) (27.3%). It was higher than the reports of Kumar et al ( 63 ) (8.15%), Yakubu et al ( 64 ) (9.23%), Atnafie et al ( 65 ) (12.38%), Mohammed et al ( 66 ) (15.89%), and Ababu et al ( 67 ) (19%).…”
Section: Discussionsupporting
confidence: 94%
“…Antibiotic resistance in E. coli O157 : H7 has been increasingly noted over the last 20 years [ 24 ]. A recent study revealed that a higher incidence rate of E. coli O157 : H7 multidrug resistance, to more than two antimicrobial agents, was observed in Ethiopia [ 9 , 25 27 ].…”
Section: Introductionmentioning
confidence: 99%